Corporate Financial Theory Under Uncertainty - Smith, Vernon L. (Quarterly Journal of Economics, 1970)
I. Debt versus equity financing, 452: Investor portfolio choice, 454; Fundamental leverage theorem, 456; Leverage as an externality 456; Effect of no default risk: the “homemade leverage theorem,” 457; Corporate management and the capital markets, 458; Corporate capital budgets as a “public good,” 460. — II. The corporate investor: long-, margin-, and short-risk positions, 462. — Appendix: option financing, 467.